Peculiarities of management of enterprises in the printing industry - Safonov, Yurii; Gutkevych, Svitlana; Shenderivska, Lina (My University, 2022)
he aim of the study is to analyze the features of management of printing enterprises, to give recommendations for business development. The significance of the printing industry in the publishing and printing complex for the formation of the intellectual capital of the nation, the development of a democratic humane and progressive society is substantiated. The factors determining the spread of small business in printing were revealed. They are related to the peculiarities of the consumer market, which requires a wide geography of supplies and personalized orders; to the development of scientific and technological progress, the result of which is the invention of less capital-intensive technologies; to the state policy focused on the stimulation of small business development. The relevance of the business model of cooperation in the publishing and printing complex at the international level has been proved. Its appropriateness is due to the small size of the domestic market, the lack of funding sources for innovation, the undeveloped domestic material and technical base. Enterprise management at the planning stage should take into account the high complexity of mastering employees CRM-systems. Understanding the strategic importance of spending time and resources on mastering new technologies and on personnel development provides synergy for the entire production system, promotes self-improvement of employees, their desire for continuous progress and, finally, increases their job satisfaction. International benchmarking is relevant to improve the management of printing companies. The authors identified funding for training of talented youth, certification of production according to international quality standards, priority of investment in innovation, search for new market niches, and strengthening of inter-sector cooperation as priorities.

Метою дослідження є аналіз особливостей управління поліграфічними підприємствами, надання рекомендацій щодо розвитку бізнесу. Обґрунтовано значення поліграфічної галузі у видавничо-поліграфічному комплексі для формування інтелектуального капіталу нації, розбудови демократичного гуманного прогресивного суспільства. Виявлено фактори, що зумовлюють поширення малого бізнесу в поліграфії. Вони пов'язані з особливостями споживчого ринку, який потребує широкої географії поставок та індивідуальних замовлень; до розвитку науково-технічного прогресу, результатом якого є винайдення менш капіталомістких технологій; до державної політики, спрямованої на стимулювання розвитку малого підприємництва. Доведено актуальність бізнес-моделі співпраці у видавничо-поліграфічному комплексі на міжнародному рівні. Його доцільність зумовлена ​​невеликим обсягом внутрішнього ринку, відсутністю джерел фінансування інноваційної діяльності, нерозвиненістю вітчизняної матеріально-технічної бази. Керівництво підприємства на етапі планування повинно враховувати високу складність освоєння співробітниками CRM-систем. Розуміння стратегічної важливості витрачання часу і ресурсів на освоєння нових технологій і розвиток персоналу забезпечує синергію всієї виробничої системи, сприяє самовдосконаленню співробітників, їх прагненню до постійного прогресу і, зрештою, підвищує задоволеність роботою. Міжнародний бенчмаркінг актуальний для покращення управління поліграфічними компаніями. Пріоритетами автори визначили фінансування навчання талановитої молоді, сертифікацію виробництва за міжнародними стандартами якості, пріоритетність інвестицій в інновації, пошук нових ринкових ніш, посилення міжгалузевої співпраці.
Keywords: кафедра міжнародної економіки; CRM systems; printing industry; поліграфія; publishing and printing company; видавничо-поліграфічне підприємство